Examining the influence of positive childhood experiences on childhood overweight and obesity using a national sample - Crouch, Elizabeth; Radcliff, Elizabeth; Kelly, Katherine; Merrell, Melinda A.; Bennett, Kevin J. (Preventive medicine, 2022)
Positive childhood experiences (PCEs) promote healthy social development, improve overall wellness, and help to moderate and prevent exposure to adverse childhood experiences. There has been limited research examining the association between positive childhood experiences and overweight or obesity status in children. The purpose of this study was to examine whether experiencing positive childhood experiences are associated with lower rates of overweight or obesity status in children between 10 and 17 years of age, using cross-sectional data from the 2018–2019 National Survey of Children's Health (n = 28,771), a nationally representative mail and online survey. Frequencies, proportions, and unadjusted associations for each variable were calculated using descriptive statistics and bivariate analyses. To examine the association between overweight or obesity and PCEs, multivariable regression models were used. Compared to children who were underweight or had a healthy weight, children who were overweight or obese were less likely to: participate after school activities (78.1%, p < 0.0001), volunteer in their community, school, or church (45.6%, p < 0.0001), have a mentor they feel comfortable going to for guidance (87.0%, p = 0.02), live in a safe neighborhood (61.3%, p < 0.0001), live in a supportive neighborhood (50.4%, p < 0.0001), and to live with a resilient family (78.3%; p = 0.0099). In adjusted analysis, among children exposed to two or more ACEs, children residing in a supportive neighborhood were less likely to be overweight or obese (aOR 0.87; 0.77–0.98). Our findings suggest that certain PCEs may mitigate overweight and obesity when children have experienced at least some childhood trauma. •Overweight or obese children were less likely to have positive experiences.•Children living in supportive neighborhoods were less likely to be overweight/obese.•Children residing below poverty level were more likely to be overweight/obese.